1984
DOI: 10.1159/000124013
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Responses of Pineal Cells to Pineal Indoles and Putative Transmitters in Intact and Blinded Pigeons

Abstract: The effects of micro-electrophoretically applied pineal indoles, melatonin (MEL), 5-methoxytryptophol (MTL) and 5-hydroxytryptophol (HTL) and of the neurotransmitters, noradrenaline (NOR), acetylcholine (ACH) and γ-aminobutyric acid (GABA) on the electrical activity of pineal cells were studied in anaesthetized pigeons. Recordings were made from both sighted and blinded birds during both the day- and night-time. Both excitatory and inhibitory responses to the application of all substances tested were observed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…It may be argued that the firing observed in our study was not endogenous but was caused by degenerating intrapineal sympathetic fibres and the resulting leakage of noradrenaline. That the firing may be principally affected by noradrenaline was shown in pigeon pineal glands in which the microiontophoretically administered substance stimulated, inhibited or did not affect the firing [24]. However, since the electrical activity we observed was uniform and followed distinct rhythmic patterns (see below), we conclude that, in our material, noradrenaline leakage did not cause the electrical events.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It may be argued that the firing observed in our study was not endogenous but was caused by degenerating intrapineal sympathetic fibres and the resulting leakage of noradrenaline. That the firing may be principally affected by noradrenaline was shown in pigeon pineal glands in which the microiontophoretically administered substance stimulated, inhibited or did not affect the firing [24]. However, since the electrical activity we observed was uniform and followed distinct rhythmic patterns (see below), we conclude that, in our material, noradrenaline leakage did not cause the electrical events.…”
Section: Discussionsupporting
confidence: 56%
“…In this context, the spiking cells may monitor extracellular neurotransmitter and hormone levels in the pineal gland and adapt their firing accordingly, as suggested for the rat [37,38]. Indeed, the spiking cells in avian pineal glands are principally capable of subserving such a function, as has been demonstrated in the pigeon pineal, in which firing is affected by noradrenaline, acetylcholine, k-aminobutyric acid, melatonin and 5-methoxytryptophol [24].…”
Section: Research Articlementioning
confidence: 93%
“…At the same time, in the studies of the effects of microelectrophoretic applications of melatonin, noradrenaline, acetylcholine, GABA, testosterone, estrone, and prolactin on the circadian rhythms of pinealocyte electrical activity in pigeons and guinea pigs [56 ] it was found that the above hormones and transmitters effectively change the discharge frequency in these cells. These data indicated that electrical activity of pinealocytes is also determined by the influence of humoral factors [57 ].…”
Section: Electrophysiology Of the Epiphysismentioning
confidence: 78%
“…Pev~t emphasized the capability of the epiphysis to uptake from the circulation system melatonin synthesized in other organs, as well as the role of this hormone as a stimulator of epiphyseal functions (synthesis of epiphyseal hormones). Therefore, an increase in the background electrical activity of the pinealocytes evoked by microapplication of melatonin, as found by Serum et al [2][3][4], could be just due to activation of peptide biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Serum et al [2][3][4] found that following microelectrophoretic application of melatonin to the pineal cells in birds and guinea pigs many pinealocites intensified their background electrical activity. Based on this observation, the authors suggested that an increase in the concentration of the proper hormone (melatonin) may enhance functional activity of the organ, i.e., a positive feedback principle is realized.…”
Section: Introductionmentioning
confidence: 99%